Examine the individual’s behavioural intentions to use Green Information technology: Moderating role of personality trait conscientiousness - GILL, DR. ATIF ALI; ANSARI, RIAZ HUSSAIN; IQBAL, SAMEERA; ASIM, JAMIL (The journal of contemporary issues in business and government, 2020)
The enormous rise in information technology (IT) usage has benefited human in numerous ways in recent years. Meanwhile, it also increases power consumption that deleteriously affects the natural resources. Environmental awareness focuses on the utilization of green Information technology (GIT) among consumers. The current article aims to examine the behaviour to use GIT based on planned behaviour theory (TPB). The data collected from university students who were familiar with GIT. Personality trait conscientiousness included as a moderator in the research model. The findings through the statistical technique of partial least square structural equation modelling (PLS-SEM) revealed that green attitude, subjective norm, and perceived behaviour control significantly impact the intention to use GIT. While conscientiousness significantly moderates the relationships between green attitude and intention to use GIT. The present study provides several implications by extending the TPB theory through the moderating effect of conscientiousness and further delivering guidelines to policymakers in higher education institutes to improve students’ personality traits for better intention towards using green information technology.